Evaluation of Training Family Health Center Practice in Family Medicine Residency Education - Nesibe Derya Bayhan; Abdulkadir Kaya (Journal of Medical Education and Family Medicine)
Objective: Tertiary hospitals offer advanced health services, including chronic disease management, whereas primary health care centers focus on services such as pregnancy follow-up, child care, vaccination, and periodic health screenings. These differing roles highlight the need for Education Family Health Centers (EHC), which are increasingly important in family medicine education. This study assesses the perceived necessity of EFHCs among family medicine specialists and residents.Methods: A descriptive cross-sectional survey was conducted among family physicians via Google Forms between February and April 2022. The survey collected sociodemographic data and assessed knowledge related to primary care. Participants’ work status in EFHCs and their performance on knowledge questions were compared.Results: The study included 263 physicians, 58.2% female and 41.8% male. Among them, 62% were married, 55.1% were full-time family medicine residents, 16.3% were contracted residents, and 28.5% were specialists. EFHC training was part of specialty education for 35% of the participants. Additionally, 18.6% had worked in EFHCs, and 15.6% had a responsible trainer. Those who had a responsible trainer in an EFHC scored significantly higher on knowledge questions (P=.049). However, no significant difference was observed in knowledge levels on the basis of the requirements of EFHC or its inclusion in specialty training.Conclusion: This study highlights the necessity of EFHCs and the crucial role of trainers within these centers. The findings suggest that integrating EFHCs into specialty training could enhance educational outcomes and better prepare family medicine residents. These findings reveal that the EASM has an important role in family medicine speciality education and that training increases the quality of education.